Improved neurosensory outcome at 8 years of age of extremely low birthweight children born in Victoria over three distinct eras - Doyle, L W; Anderson, P J (Archives of disease in childhood. Fetal and neonatal edition, 2005)
Aim: To determine neurosensory outcome at 8 years of age of extremely low birthweight (ELBW) children born in the 1990s, how it varies with birth weight, and how it compares with ELBW children born in the 1980s and 1970s. Methods: Subjects were born in the state of Victoria during 1991–92 and comprised 224 of 241 consecutive survivors with a birth weight of 500–999 g, and 223 of 262 normal birthweight (NBW) controls who had been randomly selected at birth. The comparison cohorts from earlier eras comprised 87 of 89 consecutive ELBW survivors born in 1979–80, 206 of 212 consecutive ELBW survivors born in 1985–87, and 51 of 60 randomly selected NBW survivors born in 1981–82. Survivors were assessed for neurological impairments (cerebral palsy, blindness, deafness, intellectual impairment) and disabilities at 8 years of age by paediatricians and psychologists blinded to perinatal details. Results: For the 1991–92 cohorts, the rate of neurosensory disability was substantially higher in ELBW children compared with NBW controls (p<0.0001). Within the ELBW group, neurosensory disability was more prevalent in children with a birth weight of <750 g compared with a birth weight of 750–999 g (p = 0.024). Disability rates were lower in the 1991–92 ELBW cohort compared with the ELBW cohort born in 1979–80 (p = 0.046). Conclusions: Neurosensory disability rates at school age were more common in ELBW children born in the 1990s compared with NBW controls, and were significantly more common in the 500–749 g birthweight subgroup, but have improved compared with ELBW children born in earlier eras.